EKSPERIMENTASI MODEL PEMBELAJARAN SNOWBALL THROWING DAN NHT DITINJAU DARI GAYA BELAJAR SISWA PADA MATERI HIMPUNAN KELAS VII SMP AVICENNA CILEUNGSI - Rahmawati, Nurina Kurniasari; Setiani, Setiani (Universitas Tanjungpura, 2019)
AbstractThe aim of the research was to find out the effect of learning models on mathematics achievement viewed from the student learning style. The learning model compared were snowball throwing and NHT (Numbered Head Together). The type of the research was a quasi-experimental by 2Ã—3 factorial design. The population was the seven grade student of junior high school in Cileungsi district on academic year 2017/2018. The sampling tecnique was cluster random sampling. The size of the sampel was 60 students consisted of 30 students in the first experimental group and 30 students in second experimental group. The instruments used were mathematics achievement test and learning style questionnaire. The data was analyzed using unbalanced two-way analysis of variance. The conclusions of the research were as follows. (1) Snowball Throwing learning model gives better mathematics achievement than NHT learning model, and (2) The students with visual and auditory learning style have the same mathematics achievement and give better mathematics achievement than the students with kinesthetic learning style, (3) In all the students with visual, auditory and kinesthetic learning style, snowball throwing learning model give the better mathematics achievement than NHT learning model. (4) In the snowball throwing and NHT learning models, students with auditory and visual learning style have the same mathematics achievement and have the better mathematics achievement than students with kinesthetic learning style.Keywords: Snowball throwing, NHT, learning style, mathematics achievement